2019
DOI: 10.1111/chso.12357
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Agency in the Modern Primary Classroom

Abstract: This paper examines where and how children achieve agency in the primary classroom, drawing on a multimodal ethnography of the Year One classroom. It utilises a relational conceptualisation of agency, where children act purposively to achieve outcomes of educational relevance. It demonstrates that children achieve agency performing ‘good’ and ‘clever’ child subject positions, helping to make classroom life more liveable, although this form of agency is limited when dealing with unexpected challenges. Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
0
21
1
Order By: Relevance
“…Research with younger children in schools and communities corroborates this response to such sonic experiences. Children in classrooms and communities report experiences of being quietened and stilled (Kirby 2020) and 'scolded' (Aruldoss, Nolas, and Varvantakis 2021) respectively, their teachers and other members of their communities requesting their bodily conformity (Kirby 2020), their 'good' and quiet behaviour.…”
Section: Childhood Publics In Search Of An Audiencementioning
confidence: 99%
“…Research with younger children in schools and communities corroborates this response to such sonic experiences. Children in classrooms and communities report experiences of being quietened and stilled (Kirby 2020) and 'scolded' (Aruldoss, Nolas, and Varvantakis 2021) respectively, their teachers and other members of their communities requesting their bodily conformity (Kirby 2020), their 'good' and quiet behaviour.…”
Section: Childhood Publics In Search Of An Audiencementioning
confidence: 99%
“…Agency is thus not an internal, individual capacity, but is socially situated. Societal contexts shape, enable and restrict agency (Kirby, 2020; Valentine, 2011). Children are simultaneously products of culture, and co‐constructors of culture (Ulvik & Gulbrandsen, 2019), and their personal little stories are neither determined nor totally ‘free’.…”
Section: Future‐oriented Youth Narrativesmentioning
confidence: 99%
“…People actively draw from available ‘tool‐kits’ (Lamont & Small, 2008; Swidler, 1986; Wertsch, 1998,) and use them in their narratives when making meaning of their lives (Bruner, 1990; Gulbrandsen, 2014; Hundeide, 2005). Children also have agency as active meaning makers (Brady & Gilligan, 2020; Kirby, 2020). In this meaning‐making process, the relation between agency and structure is dialectic, not binary; children have capabilities of changing, producing and reproducing their social worlds (Oswell, 2020).…”
Section: Future‐oriented Youth Narrativesmentioning
confidence: 99%
“…Structures and practices in Finnish ECEC centres are deeply entrenched (Kangas, Venninen, & Ojala, 2016; Virkki, 2015). This creates challenges in promoting children's participation and including children's initiatives and interests (Kangas & Lastikka, 2019; Kirby, 2020). Furthermore, international research has shown that official documents and law do not automatically guarantee participation in ECEC practices (Connors & Morris, 2015; Kangas, 2016; Sargeant, 2018; Webb, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that after development projects, ECEC practices can easily revert to old practices in which educators plan practices and children are seen as the objects of action (Karlsson, 2012; Nyland, 2009; Venninen, Leinonen, Lipponen, & Ojala, 2014). Thus, there is a critical need for further development and research (Kangas, 2016; Quennerstedt, 2010, 2011; Virkki, 2015) and for new structures and practices in order to develop a culture of participation and strengthen children's agency (Kangas, 2016; Kirby, 2020).…”
Section: Introductionmentioning
confidence: 99%